Urban Revitalization Of Historical Town Centre: A Case Study Of The Cultural Heritage Zone Of George Town, Penang. - Yeap , Soon Lye (1998)

(untitled)
George Town, due to its historic background, has a large pool of pre-war building and a reasonably intact historic center Among Malaysian states, Penang alone has an impressive collection of early 19th century Anglo- Indian building where British Indian architecture influences were disseminated to the rest of the Straits of Melacca. The Rent Control Act 1966, which covers private owned buildings completed before 310t January 1948, has contributed to the retention of thousands of inner city residential structures built the 19th and 20th which are rich in multicultural representation. lifestyles. religious and traditions With the issue of Malaysian Government's repeal the Rent Control Act of Malaysia (1966) by the year of 2000. this action Will threaten to bring changes. as many worship houses m the inner city of George Town are set up on rent control premises It would tear apart the last vestiges of the remaining clannish communities in george Town and the area concerned would lose then original identity Furthermore. today 's world is increasingIy dominated by' global culture Major Cities have begun to resemble due to the contemporary steel and glass buildings that fall to present the tradItion and lIfestyle of the Malaysian people Through these uncritical adoption of western Ideals.